Clinico-pathologic and immunohistochemical profiles of malignant and potentially malignant verrucopapillary lesions of the oral cavity / Syahir Hassan - Syahir , Hassan (2017)
Introduction: Verruco-papillary lesion (VPL) and non-VPL may be clinically and histologically similar. Problems separating these lesions are compounded by poorly oriented tissue sections and biopsies failing to demonstrate lesional margins. Objectives: To determine the clinico-pathologic and immunohistochemical profiles of VPL and compare it with non VPL by utilizing a set of 4 immunohistochemical panel (p53, Ki67, matrix metalloproteinase-1 (MMP-1) and E-cadherin). It is a further objective to evaluate these selected immunohistochemical panel as potential markers for differentiating between VPL and non-VPL. Methods: Twenty-four cases of VPL and twenty-nine cases of non VPL were studied. Diagnoses were confirmed by two oral pathologists. Formalin-fixed, paraffin-embedded archival tissues of these cases were used for immunohistochemistry (avidin–biotin immunoperoxidase technique) of p53, ki-67, e-cadherin and MMP-1. Results: We found that most of the VPL (70.8%) patients were 60 years and above while most of non-VPL (69%) patients were less than 60 years old (p=0.004). The male to female ratio were 1:3.8 and 1:1.4 for VPL and non VPL patients, respectively. Indian ethnic group were the highest in both VPL and non-VPL cases with betel quid chewing the most associated habit. Location wise, VPL were predominantly located on buccal mucosa (45.8%) while most of non-VPL (75.9%) cases were located on the tongue & floor of the mouth. This findings was statistically significant (p=0.001). There was a significant higher lymph node positivity in non-VPL (85.7%) compared to VPL (36%) cases (p=0.001). The nuclear staining of p53 and Ki-67 was seen in a majority of VPL compared to non-VPL cases. There was no statistically significant difference between the scores for percentage staining of these 2 markers in VPL and non-VPL. There was a diffuse membranous staining exhibiting E-cadherin expression in both VPL and non-VPL cases. A slightly lower combined percentage and intensity scores in non-VPL (96.6%) compared to VPL (100%) cases was observed. These findings are however, not statistically significant. MMP-1 expressions are seen in the cytoplasm of both VPL and non-VPL cases. There were significantly higher combined percentage and intensity score of MMP-1 in VPL (91.7%) cases compared to non-VPL (62.1%) cases (p=0.013). Conclusion: Among the four IHC markers investigated in this study, MMP-1 demonstrated a significantly high expression for VPL compared to non-VPL. Although a properly oriented hematoxylin–eosin-stained section including normal marginal tissue is considered to be the gold standard for differentiation of VPL and non-VPL potentially malignant and malignant disorders, the outcome of this study suggests that for selected markers, immunohistochemistry may serve as a useful diagnostic adjunct in interpreting the histopathology of difficult cases.